Physical Literacy and Health Education: A Systematic Review of Educational Outcomes - Andes Martua Harahap; Bintang Nurilla Panjaitan; Santa Nunut Hutasoit; Nazmi Ahmad Amin Sinambela (INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose: This systematic review examines the relationship between physical literacy (PL) and health education, with a focus on the educational outcomes generated by school-based interventions targeting students from primary through secondary levels. It aims to synthesise evidence on how PL-oriented programmes influence physical, cognitive, affective, and social dimensions of student development. Materials and Methods: Following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, five electronic databases were systematically searched: Dimensions, Scopus, Web of Science, PubMed/MEDLINE, and ERIC. Search terms combined 'physical literacy,' 'health education,' 'physical education,' 'educational outcomes,' 'learning outcomes,' and related population terms (student*, school*, adolescen*, youth). Publications were limited to 2022–2026. Independent reviewers screened and extracted data; quality was assessed using adapted ROBIS and GRADE frameworks. Results: From 1,889 records identified, 38 studies met inclusion criteria. Holistic PL interventions demonstrated consistent positive effects on the physical domain (motor competence, physical activity participation) and moderate effects on affective outcomes (self-efficacy, motivation, enjoyment). Cognitive and social outcomes showed mixed evidence. Teacher competency, implementation quality, and policy alignment emerged as critical moderating factors. Significant heterogeneity was noted across study designs, PL assessment instruments, and reported outcomes. Conclusions: Physical literacy interventions within health education contexts offer measurable benefits across several educational outcome domains, particularly for physical competence and affective development. Future research must prioritise standardised PL assessment, longitudinal designs, and equitable implementation frameworks to advance the evidence base and inform national policy.